Note taking organizer application based on #Hashtag / Shahrul Afiq Asyraaf Shahrul Azman - Shahrul Azman, Shahrul Afiq Asyraaf (2017)
This research was about developing a mobile application that allows the user to create note by adding other media content such as images and audio. Besides that this application can be search by hashtag. The hashtag act as the header or title of each note. The problem statement was the user can actually create a same title to a different note. It may be hard and time consuming for the user to search or find the previous note and some notes even end up missing. There were three objectives that need to be achieved in this project which were, to gather and analyze the requirement from the students about their way of note taking using smartphones, to design mobile application that can store note taking and some media content and to develop a Note Taking Organizer Application Based On #Hashtag. There are one actor involved in this application which is the student. This project used the System Development Life Cycle (SDLC) which consists of three phases which are the requirement gathering and analysis, the design phase and development phase with each of the phases had its own activities involved and the deliverables. Each phases achieved each objectives of the project. The findings of this project is to enable the user to search or find their notes easier by using the hashtag tagging as their header or title. The application can be used by many user from their own device. The limitations for this project is the storage of the notes itself must be reliable with the space storage of the phone. The recommendations for the project are the notes can be shared among other users in the future.